Modelling and essential control of an oceanographic monitoring remotely operated underwater vehicle - Rojas Mendoza, Jorge Enrique (2017)
Ocean pollution and contamination of the water are serious problems because of its rapid increase and spread, having a negative effect on people, animals and the environment. Due to this, new technologies to monitor and measure environmental parameters are being developed. Remotely Operated Underwater Vehicles (ROVs) have become a commonly used robotic platform in oceanographic monitoring and analysis. The ROVBWSTI, designed by Fraunhofer IOSB-AST Institute, is an underwater modular vehicle capable of fulfilling numerous tasks, especially in the area of environmental sensoring. The motion of the ROV is commanded through a joypad controller, and functional requirements of autonomy are not implemented yet. Motivated by this fact, this master thesis focuses on the modelling of the dynamics of the remotely operated vehicle, considering its motion, existing ocean currents, effects of gravitation and buoyancy. Moreover, the concrete effect of the thrusters on the ROV is analysed and identified. Furthermore, the detailed identification of the dynamic and hydrodynamic parameters required in the model is considered, based on empirical estimations, computational methods and experimental tests. The obtained approach is simulated and optimized, using real motion trials as a reference. After the successful modelling, the design of an essential control system that includes set-point regulation and waypoint tracking is performed and simulated. As a result, it obtains an accurate dynamic model of the remotely operated vehicle that was successfully simulated and compared with real motion tests. On the other hand, the proposed control system applied to the model adequately achieves its purpose of regulation and way point tracking that allows the autonomy of the vehicle.